Correlation between structural and optical properties of self - assembled In05Ga05As quantum dots - Didik Aryanto, 1983-, author; Zulkafli Othaman, author; Abd. Khamim Ismail, author; Amira Saryati Ameruddin, 1985-, author; Asian Physics Symposium (APS 2009) (3rd: 2009: Indonesia) (Skudai : Universiti Teknologi Malaysia, 2009)
PRZSL